1984
DOI: 10.1161/01.hyp.6.2_pt_2.i82
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ouabain on arteriolar responses to norepinephrine in chronic, benign, volume-expanded hypertension.

Abstract: We have reported increases in ouabain-sensitive Rb+ uptake by freshly excised conduit arteries from volume-expanded Dahl salt-sensitive (S) rats and also from rats with chronic (4 to 6 weeks), benign (serum creatinine less than 1.4 mg%) one-kidney, one clip ( 1K1C ) hypertension on high NaCl intake. To assess in vivo arteriolar function in this latter model, and a role for putative circulating ouabain-like factors, we perfused the maximally vasodilated (nitroprusside, 0.015 mg/ml limb blood), vascularly isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…Previous reports have demonstrated that higher doses of ouabain sensitize the contractile response to a-adrenergic agonists and to KCl in 1K1C rats (21,22). The same occurs with DOCA-salt rats in which ouabain treatment increased even more the pressor responses (23).…”
Section: Discussionmentioning
confidence: 57%
“…Previous reports have demonstrated that higher doses of ouabain sensitize the contractile response to a-adrenergic agonists and to KCl in 1K1C rats (21,22). The same occurs with DOCA-salt rats in which ouabain treatment increased even more the pressor responses (23).…”
Section: Discussionmentioning
confidence: 57%
“…The ouabain-like substance has received attention because of its diuretic and vasoconstrictive action mediated by the inhibitory action against Na+-K+-ATPase. In spite of many reports suggesting the existence of this substance, its physiologial role remains controversial (19)(20)(21). Pedrinelli (21) examined the pressor response to exogenous ouabain in patients with primary hyperaldosteronism and low renin essential hypertension, who are reported to have an increased level of the ouabain-like substance and found no differnce in the blood pressure response compared with normal renin essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Pedrinelli (21) examined the pressor response to exogenous ouabain in patients with primary hyperaldosteronism and low renin essential hypertension, who are reported to have an increased level of the ouabain-like substance and found no differnce in the blood pressure response compared with normal renin essential hypertension. Overbeck (19,20) also reported no evidence for the physiological role of this substance in the pathogenesis or maintenance in early and chronic stages of Goldblatt hypertension models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences have important and complex influences on vascular responses to norepinephrine, 14 influences that make data interpretation difficult. In some rats we used adenosine injections and then infusions to evoke and maintain maximal vasodilation.…”
Section: S Everal Laboratories Have Provided Evidencementioning
confidence: 99%